A CRITICAL ANALYSIS OF THE RELIGIOUS MODERATION POLICY IN ISLAMIC EDUCATION: RESISTANCE AND SYMBOLIC VIOLENCE IN EDUCATIONAL INSTITUTIONS - Rikhlatul Ilmiah; Kadi Kadi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to critically examine the politics behind the government's policy on religious moderation within the context of Islamic religious education. Initially intended as a response to the rise of radicalism in Islamic religious education in Indonesia, the policy has instead transformed into another form of radicalism, driven by grassroots fanaticism and the rigid implementation of religious moderation by government institutions—particularly the Ministry of Religious Affairs. These institutions tend to eliminate ideas deemed radical or threatening to state stability without providing space for dialogue or seeking common ground. Using a qualitative approach through a literature review method, this study finds that the infiltration of religious moderation into the Islamic education curriculum is a political strategy by the state to hegemonize the Muslim community and suppress groups considered disruptive to national political stability. However, this effort has triggered resistance and symbolic violence among the public and educational institutions. The findings imply the urgent need for the government to reform the administration of Islamic religious education to ensure that religious moderation does not become a tool of symbolic violence: (1) the government must detach its political interests from religious education, (2) implement inclusive Islamic education across different schools of thought (madhhab) to foster a strong sense of moderation among students, and (3) minimize symbolic violence in religious education, as it contradicts the very values of religious moderation itself.